A Study on Customer Satisfaction on Online Marketing in India - Chitra, S; Shobana, E (International Research Journal of Management, IT & Social Sciences, 2017)
Marketing of products or services over the internet. Online Marketing is the marketing of products or services over the internet & it ties together creative and technical aspects of the internet, including design, development, advertising and sale. Online marketing is used by companies selling goods and services directly to consumers as well as those who operate on a business to business. Online marketing, it refers to the techniques which is available to a business market, promote and advertise their products, services or brand to the World Wide Web.